2021
DOI: 10.34172/jcs.2021.030
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pre-operative Nutritional Protocol Implementation on Postoperative Outcomes Following Gastrointestinal Surgeries: A Randomized Clinical Trial

Abstract: Introduction: A significant proportion of patients undergoing major gastrointestinal operations suffer from malnutrition. Although the benefit of postoperative nutritional support is well established, the effects of energy intake during pre-operative period is less reported. The present study was designed to test the effect of structured pre-operative nutritional therapy on the postoperative recovery of patients undergoing major gastrointestinal operations. Methods: A randomized clinical trial was conducted am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
2
0
1
Order By: Relevance
“…Die Anwendung von Ernährungsprotokollen und Standardarbeitsanweisungen (SOP) hat sich als vorteilhaft für die Sicherstellung der Durchführung der medizinischen Ernährung und das Erreichen des Kalorienziels gezeigt 302 303 (2+ und 1+) Eine angemessene Versorgung mit Mikronährstoffen wird als wesentlich für eine langfristige totale PE angesehen. Bhattacharyya haben randomisiert positive Auswirkungen eines präoperativen Protokolls auf das Eintreten der Darmtätigkeit und den Beginn einer EE gezeigt 304 (1-).…”
Section: Indikation Zur Ernährungstherapieunclassified
“…Die Anwendung von Ernährungsprotokollen und Standardarbeitsanweisungen (SOP) hat sich als vorteilhaft für die Sicherstellung der Durchführung der medizinischen Ernährung und das Erreichen des Kalorienziels gezeigt 302 303 (2+ und 1+) Eine angemessene Versorgung mit Mikronährstoffen wird als wesentlich für eine langfristige totale PE angesehen. Bhattacharyya haben randomisiert positive Auswirkungen eines präoperativen Protokolls auf das Eintreten der Darmtätigkeit und den Beginn einer EE gezeigt 304 (1-).…”
Section: Indikation Zur Ernährungstherapieunclassified
“…The implementation of nutritional intervention is directly related to postoperative clinical outcomes. Nutritional therapy for 7-14 days prior to the surgical procedure has consistently showed to improved clinical outcomes [1,7]. As such, this preoperative window of opportunity is key to prescribe nutritional therapy that can ultimately lead to better postsurgical outcomes.…”
Section: Preoperative Nutritional Interventionmentioning
confidence: 99%
“…As a result, the prevalence of malnutrition associated or not to sarcopenia may increase during the early postoperative period. This is commonly observed preoperatively, especially in oncological patients, and leads to an increased risk of postoperative complications, length of hospital stay (LOS), and costs [1][2][3]. Several studies have shown that the implementation of multimodal protocols of enhanced recovery is essential to reduce unfavorable postoperative outcome.…”
Section: Introductionmentioning
confidence: 99%